Civil Legal Protection Against Patients For Chatbot-Based Health Consultation Malpractice - Andi Hartawati; A. Silfiana Sirajuddin; MUHAMMAD SUMARDIN (Leges Privatae, 2025)
The advancement of artificial intelligence (AI) in the healthcare sector has significantly transformed medical consultation practices, particularly through the use of AI chatbots as tools for preliminary diagnosis and health recommendations. However, the use of such systems introduces potential algorithmic errors and biases that may cause harm to patients, while the existing legal framework has not yet clearly defined the scope of civil liability in cases of AI-based malpractice. This study employs a normative juridical method with statutory, conceptual, and comparative approaches to examine civil legal protection for patients harmed by AI-driven medical consultations. The findings reveal that Indonesia’s Health Law, Consumer Protection Law, and Electronic Information and Transactions Law remain insufficient to address the complex distribution of liability among doctors, healthcare institutions, platform providers, and AI developers. Therefore, regulatory reform in the form of a lex specialis is necessary to incorporate the principles of explainability, mandatory algorithm auditing, and burden-shifting mechanisms to ensure equitable legal protection for patients in the digital era.